Treating Childhood Psychopathology and Developmental - Andrasik, Frank (2017)
Child psychology is a constantly expanding field, with dozens of specialized journals devoted to major disorders springing up in recent years. With so much information available – and the prospect of overload inevitable – researchers and clinicians alike need to navigate the knowledge base with as much confidence as they do the nuances of diagnosis and their young clients’ complex social, emotional, and developmental worlds.